Effect of local orientation cues on discrimination of periodic motion trajectories - Ng, Eng Chuan (Nanyang Technological University, 2020)
Radial frequency (RF) motion trajectories are stimuli that involve a dot moving through a radially deformed path, and are employed as a tool to study periodic motion (Or, Thabet, Wilkinson, & Wilson, 2011). Periodic motion is further explored by the inclusion of local orientation cues into these RF motion trajectories. Participants observed a Gabor element moving on a trajectory around a fixation point, and had to discriminate between circular and RF trajectory in a two-interval forced choice (2IFC) task. In this study, RF trajectories of 2—5 cycles were tested. The Gabor elements underwent constant rotation, such that their orientation was always parallel (collinear) or radial (orthogonal) to a circular path. The element movement speed was also varied between an angular (3.14 deg/s) and Cartesian (3.14 deg/s) speed to investigate any possible orientation-speed interactions. It was found that detection performance did not vary much between parallel and radial orientations, as well as between angular and Cartesian speed conditions. These findings suggest that orientation and speed do not cause any significant variance in detection thresholds, and that detection performance still improves according to a power-law function of RF even with the addition of local orientation cues.